Individual differences in the habitual use of cognitive reappraisal predict the reward-related processing - Sai, Liyang; Wang, Sisi; Ward, Anne; Ku, Yixuan; Sang, Biao (Frontiers in Psychology, 2015)
Recent studies have shown that instructed cognitive reappraisal can regulate the neural processing of reward. However, it is still unclear whether the habitual use of cognitive reappraisal in everyday life can influence brain activity associated with reward processing. In the present study, participant’s neural responses to reward were measured using electroencephalography (EEG) recorded during a gambling task, while their tendency to use cognitive reappraisal was assessed using the Emotion Regulation Questionnaire (ERQ). Event-related potential (ERP) results indicated that losses on the gambling task elicited greater negative reward-related feedback negativity (FN) than gains. The differential FN between losses and gains was significantly correlated with cognitive reappraisal scores across participants, such that individuals with a higher tendency to use cognitive reappraisal showed stronger reward processing (i.e. amplified FN difference between losses and gains). This correlation remained significant after controlling for expressive suppression scores. However, expressive suppression per se was not correlated with FN differences. Taken together, these results suggest that the habitual use of cognitive reappraisal influences the neural processing of reward.